2017
DOI: 10.3389/fendo.2017.00360
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Cyclophilin B Levels Are Associated with the Prevalence and Severity of Metabolic Syndrome

Abstract: ObjectiveInflammation plays a central role in the pathogenesis of metabolic syndrome (MetS). Cyclophilin B (CypB) can be constitutively secreted in response to inflammatory stimuli and oxidative stress, participating in tissue or systemic inflammation. We investigated the relationship between CypB and MetS in both humans and mice.MethodsSerum CypB levels were determined in 211 subjects with MetS and 292 subjects without MetS (non-MetS) (133 healthy controls and 159 high-risk subjects with one to two MetS compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 39 publications
2
24
0
Order By: Relevance
“…Viruses integrate cyclophilin A and cyclophilin B in their virions and further can bind and either infect cells via CD147 or activate CD147 signaling 10‐12 . We found that expression of both cyclophilins ( PPIA and PPIB ) is increased in subjects with hypertension and obesity and PPIA correlated positively with BMI in the whole blood, which is confirmed in other studies 64 . In addition, nsp1 protein of SARS‐CoV binds to CD147 via cyclophilins and reduces interferon responses 24 in infected cells.…”
Section: Discussionsupporting
confidence: 87%
“…Viruses integrate cyclophilin A and cyclophilin B in their virions and further can bind and either infect cells via CD147 or activate CD147 signaling 10‐12 . We found that expression of both cyclophilins ( PPIA and PPIB ) is increased in subjects with hypertension and obesity and PPIA correlated positively with BMI in the whole blood, which is confirmed in other studies 64 . In addition, nsp1 protein of SARS‐CoV binds to CD147 via cyclophilins and reduces interferon responses 24 in infected cells.…”
Section: Discussionsupporting
confidence: 87%
“…CypB has a crucial role against ROS and pro-inflammatory status, and their levels were associated with metabolic syndrome, vascular function and heart failure [ 2 , 6 ]. Even though, in our study, we do not find any difference between CAD patients and controls in CypB levels.…”
Section: Discussionmentioning
confidence: 99%
“…Cyps are some of the most conserved proteins present in eukaryotes and prokaryotes, and they have been implicated in diverse cellular processes and responses to multiple biotic and abiotic stresses [ 3 ]. Some of these proteins, such as CypA, CypB, CypD or FKBP51, have been previously associated with CAD [ 4 - 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, genetic knockout of Cyp A decreased adipocyte size and fat mass in mice fed a normal diet, and reduced the weight of mice administered a high fat diet [116]. Cyclophilin B (Cyp B) also is pro-inflammatory when secreted, and serum levels of Cyp B are elevated in HFD-fed mice and in people with metabolic syndrome compared to healthy controls [117].…”
Section: Cyclophilin Involvement In Mitochondrial Metabolismmentioning
confidence: 99%
“…Cyclophilin B, predominantly an ER protein, is also secreted in certain injury states by unknown mechanisms. Serum levels of Cyp A or B are elevated in many disease states including NAFLD, NASH, metabolic syndrome, and type 2 diabetes [113][114][115]117,[187][188][189][190][191][192]. In the extracellular milieu cyclophilins act both as leukocyte chemoattractants and as pro-inflammatory cytokines by binding to the transmembrane receptor, CD147 (EMMPRIN), and perhaps other receptors on granulocytes, monocytes, and CD4 T cells [193][194][195][196][197].…”
Section: Cyclophilin Involvement In Inflammationmentioning
confidence: 99%